Pengembangan Laboratorium Virtual Gelombang Bunyi Berbasis HTML5, CSS, Dan JavaScript - Ahmad Fadli; Ni Nyoman Sri Putu Verawati; Jannatin 'Ardhuha (Universitas Hamzanwadi, 2022)
This development research aims to produce and test the validity and practicality of the product in the form of a sound wave virtual laboratory so that it can be used as a learning support. Sound wave is an abstract physics concept. The type of research used in this research is research and development with research design, namely research on the development of 4D models (Define, Design, Develop and Disseminate). The define stage includes initial and final analysis, user analysis and device requirements analysis. The design stage includes the initial design of the virtual laboratory, format selection and design improvements. The develop stage includes product creation, product validation, product revision, limited trials. The disseminate stage is carried out by distributing the virtual laboratory by uploading to the website the sound wave virtual laboratory which is developed based on HTML, CSS, and JavaScript. The validity of the virtual laboratory was calculated using CVI with the acquisition of expert validators and practitioner validators of 0.96 with valid criteria. While the reliability of the virtual laboratory is calculated using the percentage of agreement with the acquisition of expert validators and practitioner validators 92.06% in the reliable category. The results of the practicality of the virtual laboratory based on student responses showed results of 84.38% in the very practical category. Thus the sound wave virtual laboratory based on HTML 5, CSS, and JavaScript is valid and very practical to use to support high school physics learning.